Spillover effects and other determinants of medical device uptake in the presence of a medical guideline: An analysis of drug-eluting stents in Germany and Italy - Meilin Möllenkamp; Benedetta Pongiglione; Stefan Rabbe; Aleksandra Torbica; Jonas Schreyögg (Health Economics, 2022)
We investigated the role of spillover effects among hospitals in the diffusion of drug-eluting stents (DES) in Germany and Italy during a period in which the relevant medical guideline clearly recommended their use over bare-metal stents. We used administrative data of hospitalized patients treated with ST-elevation myocardial infarction from 2012 to 2016 to estimate spatial panel models allowing for global spillover effects. We used an inverse-distance weights matrix to capture the geographical proximity between neighboring hospitals and assigned a lower weight to more distant neighbors. For both countries, we found significant positive spatial autocorrelation in most years based on the global Moran's I test, and a significant, positive spatial lag parameter across model specifications, indicating positive spillover effects among neighboring hospitals. We found that private for-profit hospital ownership and hospital competition in Germany and the number of inpatient cases with circulatory system diseases in Italy were other significant determinants of DES adoption. Our results underline the importance of spillover effects among peers for the diffusion of medical devices even in the presence of a positive guideline recommendation. Policymakers might therefore consider promoting various forms of exchange and collaboration among medical staff and hospitals to ensure the appropriate use of medical technologies.
Keywords: 330; adaptation; diffusion; healthcare; hospital; international comparisons; medical devices; medical guidelines; spatial panel data analysis; spillover effects; technology